Targeting cancer stem cells from a metabolic perspective. Issue 5 (March 2020) - Shen, Yao-An; Pan, Siao-Cian; Chu, I; Lai, Ruo-Yun; Wei, Yau-Huei
The process of cancer development and progression is driven by distinct subsets of cancer stem cells (CSCs) that contribute the self-renewal capacity as the major impetus to the metastatic dissemination and main impediments in cancer treatment. Given that CSCs are so scarce in the tumor mass, there are debatable points on the metabolic signatures of CSCs. As opposed to differentiated tumor progenies, CSCs display exquisite patterns of metabolism that, depending on the type of cancer, predominately rely on glycolysis, oxidative metabolism of glutamine, fatty acids, or amino acids for ATP production. Metabolic heterogeneity of CSCs, which attributes to differences in type and microenvironment of tumors, confers CSCs to have the plasticity to cope with the endogenous mitochondrial stress and exogenous microenvironment. In essence, CSCs and normal stem cells are like mirror images of each other in terms of metabolism. To achieve reprogramming, CSCs not only need to upregulate their metabolic engine for self-renewal and defense mechanism, but also expedite the antioxidant defense to sustain the redox homeostasis. In the context of these pathways, this review portrays the connection between the metabolic features of CSCs and cancer stemness. Identification of the metabolic features in conferring resistance to anticancer treatment dictated by CSCs can enhance the opportunity to open up a new therapeutic dimension, which might not only improve the effectiveness of cancer therapies but also annihilate the whole tumor without recurrence. Henceforth, we highlight current findings of potential therapeutic targets for the design of alternative strategies to compromise the growth, drug resistance, and metastasis of CSCs by altering their metabolic phenotypes. Perturbing the versatile skills of CSCs by barricading metabolic signaling might bring about plentiful approaches to discover novel therapeutic targets for clinical application in cancer treatments. Impact statement: This minireview highlights the current evidence on the mechanisms of pivotal metabolic pathways that attribute to cancer stem cells (CSCs) with a special focus on developing metabolic strategies of anticancer treatment that can be exploited in preclinical and clinical settings. Specific metabolic inhibitors that can overwhelm the properties of CSCs may impede tumor recurrence and metastasis, and potentially achieve a permanent cure of cancer patients.